2020
DOI: 10.1186/s12872-020-01770-0
|View full text |Cite
|
Sign up to set email alerts
|

Lung tumor presenting with acute myocardial infarction and lower extremity arterial embolism

Abstract: Background Lung tumor embolization leading to acute myocardial infarction (AMI) is rare. Previouscases of lung tumor embolization were reported in the coronary artery. We describe here a case of lung tumor embolization leading to the simultaneous occurrence of AMI and lower extremity arterial embolism. Case presentation A 64-year-old patient was admitted to the emergency department complaining of chest pain and was diagnosed with AMI.An echocardiography showed a mass in the left atrium that was speculated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Some studies have reported that advanced lung cancer should be considered to be a differential diagnosis of arterial embolism. 3 , 5 7 ) The present case had a highly mobile mass in the LA, which was responsible for acute lower extremity ischemia. Since the mass could result in thrombus formation in the LA, we conducted echocardiography to confirm that it originated from the primary lung cancer with continuity.…”
Section: Discussionmentioning
confidence: 69%
“…Some studies have reported that advanced lung cancer should be considered to be a differential diagnosis of arterial embolism. 3 , 5 7 ) The present case had a highly mobile mass in the LA, which was responsible for acute lower extremity ischemia. Since the mass could result in thrombus formation in the LA, we conducted echocardiography to confirm that it originated from the primary lung cancer with continuity.…”
Section: Discussionmentioning
confidence: 69%
“…Discharged. Morbidity with stroke Liu et al [ 18 ] Lung cancer Invasion into left atrium Coronary artery (Acute MI) Acute limb ischemia Treatment abandoned Death Herbert et al [ 19 ] Left Atrial Myxoma Cerebral white matter Left popliteal artery Surgical excision Discharged Murugan et al [ 20 ] Invasive ductal Breast cancer Liver metastases Pulmonary artery Thrombolysis Death Hattori et al [ 21 ] Adenocarcinoma of prostate Haematogenous metastases Pulmonary artery (on autopsy) Death Yoshikawa et al [ 22 ] Pleomorphic Lung cancer Vascular invasion Right middle cerebral artery Mechanical embolectomy Successful revascularisation. Morbidity due to stroke Oyama et al [ 23 ] Mucoepidermoid Lung cancer Right pulmonary vein and left atrium invasion Distal left internal carotid artery Mechanical thrombectomy Successful revascularisation Death Mouadili et al [ 24 ] Left atrial Myxoma Left femoral artery Right distal popliteal artery Bilateral embolectomy Surgical excision Successful revascularisation.…”
Section: Resultsmentioning
confidence: 99%
“…Several mechanisms of MI in cancer patients have been proposed [ 14 , 15 , 16 ]. The metastases of lung cancer to the heart can block coronary arteries directly, causing acute myocardial infarctions.…”
Section: Discussionmentioning
confidence: 99%
“…There is a possibility that such a situation does exist, although it is relatively rare. In the literature, several cases of myocardial infarction associated with metastatic lung cancer have been reported [ 14 , 15 , 16 ]. As the patient we describe here did not have a diagnosed metastatic disease, we may suspect that COVID-19 and the accumulation of the patient’s other traditional risk factors (smoking, diabetes type 2, hyperlipidaemia, and hypertension) could have contributed to the MI.…”
Section: Discussionmentioning
confidence: 99%